IMPLEMENTASI KEBIJAKAN PEMERINTAH DALAM PROGRAM POSYANDU DI DESA GENTEGWETAN KECAMATAN GENTENG KABUPATEN BANYUWANGI - Syamsul Arifin; Ansari Ansari (Department of Islamic Community Development, Faculty of Dakwah,Universitas Islam Ibrahimy Banyuwangi, 2025)
The existence of posyandu is widespread in all corners of the country and is a type of public health service that has strategic value to be managed and developed optimally because it is considered the spearhead of integrated activities in the community. The research method uses a descriptive qualitative approach, while the data source uses primary data and secondary data. The primary data is the Regulation of the Minister of Home Affairs Number 19 of 2011 concerning guidelines for the formation of an operational working group for the development of integrated service posts. While secondary data is obtained from a number of information obtained indirectly and data is obtained by quoting from sources such as books, magazines, journals and the internet. Data collection techniques are observation, interviews, and documentation. Meanwhile, data analysis uses several stages, namely; data collection, data reduction, data presentation, and data verification. The results of the study show that the government's implementation in the Posyandu program, namely the target group, is able to be part of the stakeholders in the Posyandu policy by providing financial resources and facilities and infrastructure resulting from non-governmental organizations. The government's obstacles in implementing the posyandu program in Gentegwetan Village, lack of human resources, lack of participation of parents in considering their children to posyandu, and lack of facilities and infrastructure of posyandu. Meanwhile, the efforts made by the government are; increasing cooperation with the Health Office, fostering posyandu cadres, increasing socialization to the community and improving posyandu facilities and infrastructure.